Synthesis of glycol diesters through the depolymerization of polyethylene glycols with carboxylic acids using a proton-exchanged montmorillonite catalyst. Issue 9 (28th February 2018) - Maeno, Zen; Midogochi, Kaoru; Mitsudome, Takato; Mizugaki, Tomoo; Jitsukawa, Koichiro
Graphical abstract: Highlights: Simple and sustainable method for synthesizing glycols is developed. It involves depolymerization of polyethylene glycols with carboxylic acids. Proton-exchanged montmorillonite is employed as an efficient solid acid catalyst. Several functionalized glycol diesters are successfully obtained in good yields. Catalyst can be separated by filtration and reused with maintaining its activity. Abstract: A convenient and sustainable method for the synthesis of glycol diesters was developed through the depolymerization of polyethylene glycols (PEGs) with carboxylic acids using proton-exchanged montmorillonite as an efficient solid acid catalyst. Several functionalized glycol diesters were obtained in good yields from PEGs and readily available carboxylic acids. Upon reaction completion, the catalyst could be easily separated by filtration and reused with its activity remaining unchanged.